Enhancing Activity for the Oxygen Evolution Reaction: The Beneficial Interaction of Gold with Manganese and Cobalt Oxides. Issue 1 (6th November 2014) - Frydendal, Rasmus; Busch, Michael; Halck, Niels B.; Paoli, Elisa A.; Krtil, Petr; Chorkendorff, Ib; Rossmeisl, Jan
Abstract Electrochemical production of hydrogen, facilitated in electrolyzers, holds great promise for energy storage and solar fuel production. A bottleneck in the process is the catalysis of the oxygen evolution reaction, involving the transfer of four electrons. The challenge is that the binding energies of all reaction intermediates cannot be optimized individually. However, experimental investigations have shown that drastic improvements can be realized for manganese and cobalt‐based oxides if gold is added to the surface or used as substrate. We propose an explanation for these enhancements based on a hydrogen acceptor concept. This concept comprises a stabilization of an *OOH intermediate, which effectively lowers the potential needed for breaking bonds to the surface. On this basis, we investigate the interactions between the oxides and gold by using DFT calculations. The results suggest that the oxygen evolution reaction overpotential decreases by 100–300 mV for manganese oxides and 100 mV for cobalt oxides.